Impact of Work Stress on Surgeons Job Satisfaction with the Moderating Effect of Social Support: An Empirical Study from the Surgeons of Private Hospitals - Dr. Jehanzaib Khan; Dr. Imran Manzoor; Dr. Rizwan Khan Lodhi; Ayesha Manzoor (Journal of Management Practices, Humanities and Social Sciences, 2023)
The purpose of this research is to investigate the relationship between work-life balance and workplace anxiety on job satisfaction experienced by surgeons. Further, the objective of this study is to investigate the moderating role of social capital among the observed variables. The researchers used quantitative methodology to conduct this research. The population of this research consists of surgeons working in private hospitals in Lahore. The researchers collected data from 495 respondents through an adopted structured questionnaire. The researchers used a simple random method to select the respondents. The findings of current research indicated that both dimensions of work stress, i.e., work-life balance and workplace anxiety, on job satisfaction. Further, the findings indicated that social capital has a moderating effect on work-life balance and job satisfaction. Lastly, the outcomes revealed that social capital has a moderating effect on workplace anxiety and job satisfaction. The study findings recommended that top-level managers have the potential to boost surgeons’ satisfaction by implementing stress management practices in the workplace and offering social support. It is possible that in the future, research will support organizational citizenship behavior as a mediator between the stress of work and the level of job satisfaction experienced by surgeons.